For Whom Do Unstructured Activities Matters? The Interaction Between Unstructured and Structured Activities in Delinquency and Cannabis Use : A National Self-Report Study - Svensson, Robert; Moeller, Kim; Johnson, Björn ; 0000-0002-1601-2706; Shannon, David (Crime and delinquency, 2023)
This study examines whether unstructured and structured activities interact in their association with delinquency and cannabis use. We hypothesize that unstructured activities are more strongly associated with delinquency and cannabis use for those who are less engaged in structured activities. Data are drawn from three nationally representative self-report studies conducted between 2005 and 2011 in Sweden, and include 19,644 adolescents. The results support the hypothesis that unstructured activities interact with structured activities in the association with delinquency and cannabis use. The association between unstructured activities and these outcomes is stronger for those with lower levels of structured activities. Sporting activities constitute the structured activity that most clearly interacts with unstructured activities in the association with delinquency and cannabis use.
2025-02-11T18:34:14.355+01:00
Keywords: unstructured activities; structured activities; sports; delinquency; cannabis use; Drug Abuse and Addiction; Beroendelära och missbruk